SISTEM ABSENSI MENGGUNAKAN SCAN QR CODE BERBASIS ANDROID - Muhammad Azmi; Muhammad Khairul Faridi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
Attendance is an important part of every educational institution. Where attendance is one of the main supports that can support and motivate every activity carried out. Like attendance at SMK Negeri 1 Sambelia which still uses the manual method (signature), this method is very vulnerable for an educational institution because of the level of discipline that cannot be controlled and can be misused by irresponsible people, other losses that may arise in manual attendance system is a data recapitulation that still takes a lot of time and effort. The purpose of this study is to design and build an android application that makes it easier for teachers to carry out the attendance process at school, the type of research used is qualitative and the results of this study are applications that utilize the Qr Code as the main component in helping the attendance process. The research method in this study is qualitative research where the data obtained are mostly descriptive of the observations that have been made, then the data will be analyzed qualitatively and described in descriptive form. Based on the test results, it can be concluded that this application still has many shortcomings that need to be developed again, it is very necessary for the role of IT students to help the development of digital technology in making attendance easier. Based on the application testing that has been carried out, the presentations of Strongly Agree 22.2%, Agree = 38.8%, Neutral = 25.9%, Disagree = 6.4%. Based on the presentation, the application made is quite good, although there are some shortcomings that must be improved.